The Role and Function of Single Parents in Special Needs Children to Combat Loneliness - Royke Tony Kalalo (Faculty of Medicine, Universitas Airlangga, 2024)
Introduction: Caring for children with special needs often poses various challenges, including coping with stress in parenting. Single parents have an even increased vulnerability to stressful conditions in parenting, especially from feelings of loneliness and alienation. This literature review aims to obtain an effective intervention model for overcoming loneliness for single parents with special needs children. Methods: Various studies were searched with the keywords “role of a single parent,” “function of a single parent,” “children with special needs,” and “loneliness.” Selected studies are evaluated and critically reviewed. Results: Various challenges of parenting children with special needs include stigma, efforts to overcome communication and behavior problems of children, adjustments to parenting according to special needs conditions, economic burdens, and intrapersonal problems of single parents. These challenges can be significant stressors that further degrade the quality of life of single parents and their children. However, they can be opportunities for personality development and parenting skills through self-care efforts and seeking psychiatric help, including efforts to find a community that understands the experience of being a single parent. Conclusions: Efforts to help single parents cope with loneliness include improving self-efficacy, emotional stability, positive parenting, and social intelligence by being part of a supportive community. Keywords: Single Parent, Children, Special Needs, Loneliness, Psychological Wellbeing